Evaluation of internship programs abroad at universities in Indonesia: A case study of Indonesian intern students in Japan - Haryanti, Pitri; Suryadimulya, Agus Suherman; Dienaputra, Reiza; Nur, Tajudin (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to evaluate internship programs in Japan held by Japanese departments at universities in Indonesia as an implementation of the Indonesian Ministry of Education and Culture's policy on independent study on campuses in 2020, examining the students’ culture shock level and the difficulties they encountered during the internship program. This study used a mixed-methods approach with case studies. We used quantitative data to measure the students’ culture shock level, and qualitative data to uncover the difficulties they encountered. Data were collected through a questionnaire, and a semi-structured interview with 100 intern students took place. This research found that Indonesian intern students’ culture shock was at a moderate level and encountered difficulties due to language, job performance, Japanese work culture, negative local attitude toward intern students, and the intern's personalities such as low adaptability and lack of confidence. This study also found that all of the students at each level of culture shock faced difficulties in performing jobs because of their low Japanese ability and work culture differences, but student personalities and locals’s responses are the determinants of the student’s culture shock level. The implications of this study highlight the need for an evaluation of Japanese language and culture learning curricula and methods in Indonesia.